2021
DOI: 10.1155/2021/5083302
|View full text |Cite
|
Sign up to set email alerts
|

Alkannin Inhibits the Development of Ovarian Cancer by Affecting miR-4461

Abstract: Background. Previous studies have shown that alkannin has anticancer, anti-inflammatory, and antibacterial effects. However, the effect of alkannin in the development of ovarian cancer (OC) remains unknown. Therefore, this study aims to elucidate the function of alkannin in OC progression. Methods. RT-qPCR and western blot analysis were used to measure mRNA and protein expression. Cell viability and metastasis were detected by the CCK-8 assay, flow cytometry analysis, and transwell assay. Results. Alkannin had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Our study found that alkannin inhibited the activation of AKT signaling by upregulating PTEN. Regarding how alkannin regulates PTEN, previous reports suggested that alkannin reduces the expression levels of some microRNAs, including miR‐4461, miR‐199a, and miR‐9, that have been reported to target PTEN 7,8,23,31–33 . Hence, we speculated that alkannin might regulate PTEN expression through multiple pathways, such as the miRNA–mRNA axis.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our study found that alkannin inhibited the activation of AKT signaling by upregulating PTEN. Regarding how alkannin regulates PTEN, previous reports suggested that alkannin reduces the expression levels of some microRNAs, including miR‐4461, miR‐199a, and miR‐9, that have been reported to target PTEN 7,8,23,31–33 . Hence, we speculated that alkannin might regulate PTEN expression through multiple pathways, such as the miRNA–mRNA axis.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding how alkannin regulates PTEN, previous reports suggested that alkannin reduces the expression levels of some microRNAs, including miR-4461, miR-199a, and miR-9, that have been reported to target PTEN. 7,8,23,[31][32][33] Hence, we speculated that alkannin might regulate PTEN expression through multiple pathways, such as the miRNA-mRNA axis. The detailed mechanism of alkannin in CSCC needs to be clarified by performing more in-depth experiments in the future.…”
Section: Alkannin Promoted Pten Expression In Cscc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prognosis for metastatic CRC is poor, with an average survival of around 30 months [6,7], underscoring the urgent need for novel therapeutic strategies. Shikonin (SHK), a naphthoquinone compound isolated from Lithospermum erythrorhizon [8,9], displays notable antimicrobial, anti-inflammatory, and antioxidant properties [10,11]. Its broad-spectrum anti-tumor efficacy has been validated, as seen in Wang et al's study on ovarian cancer [9] and Mao et al's research on oral squamous carcinoma [12].…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin (SHK), a naphthoquinone compound isolated from Lithospermum erythrorhizon [8,9], displays notable antimicrobial, anti-inflammatory, and antioxidant properties [10,11]. Its broad-spectrum anti-tumor efficacy has been validated, as seen in Wang et al's study on ovarian cancer [9] and Mao et al's research on oral squamous carcinoma [12]. Specifically in CRC, SHK has shown potential in inducing ROS and oxidative DNA damage [13], and in promoting apoptosis and cell cycle arrest [14].…”
Section: Introductionmentioning
confidence: 99%